REGULATION OF FOREIGN ECONOMIC ACTIVITY (Journal of Science-Innovative Research in Uzbekistan, 2024)
The regulation of foreign economic activity plays a pivotal role in shaping the global economic landscape. As nations continue to engage in cross border trade, investment, and collaboration, the need for effective regulatory frameworks becomes increasingly imperative. This scientific article provides a comprehensive analysis of the mechanisms, challenges, and trends associated with the regulation of foreign economic activity. Drawing upon a multidisciplinary approach, we explore the legal, economic, and political dimensions of foreign economic regulation, offering insights into the dynamic nature of international commerce